2015
DOI: 10.1557/mrc.2015.27
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and thin-film self-assembly of radical-containing diblock copolymers

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…37 We previously reported the formation of electrochemically active micelles with a polystyrene (PS) insoluble core and PTMA soluble coronal chains using PTMA-b-PS diblock copolymers dissolved in commonly used Li-ion battery electrolytes. 39 In 2014, Nishide and Suga reported the synthesis of pendant radicaland ion-containing block copolymers. 39 In 2014, Nishide and Suga reported the synthesis of pendant radicaland ion-containing block copolymers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…37 We previously reported the formation of electrochemically active micelles with a polystyrene (PS) insoluble core and PTMA soluble coronal chains using PTMA-b-PS diblock copolymers dissolved in commonly used Li-ion battery electrolytes. 39 In 2014, Nishide and Suga reported the synthesis of pendant radicaland ion-containing block copolymers. 39 In 2014, Nishide and Suga reported the synthesis of pendant radicaland ion-containing block copolymers.…”
Section: Introductionmentioning
confidence: 99%
“…38 For self-assembly in thin lms, Boudouris et al reported the possibility to form thin lms with tailored morphologies from polydimethylsiloxane-block-PTMA (PDMS-b-PTMA) diblock copolymers using solvent vapour annealing in CHCl 3 . 39 In 2014, Nishide and Suga reported the synthesis of pendant radical-and ion-containing block copolymers. The self-assembled thin lms exhibit different morphologies from spheres to inverse spheres and were used as an active layer in a diode-structured thin-lm device, combining the redox-active radicals of one block to the charge-compensating ions of the other one.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, electrolyte‐supported radical polymer systems have extremely useful transport properties, as the liquid‐based electrolytes provide ample mobility to the radical polymer pendant groups. On the other hand, only recently was it established that these types of reactions can also occur in a rather rapid manner in solid‐state organic electronic applications . Specifically, the model radical polymer, poly(2,2,6,6‐tetramethylpiperidinyloxy methacrylate) (PTMA), is an extraordinarily transparent material and can be easily synthesized in large batches .…”
Section: Introductionmentioning
confidence: 99%
“…This allowed for easy visualization of the self‐assembled thin films in the atomic force microscope (AFM). Additionally, our group showed that PTMPM could be grown from bromine‐terminated poly(dimethyl siloxane) (PDMS) to generate poly(dimethyl siloxane)‐ b ‐poly(2,2,6,6‐tetramethylpiperidine‐4‐yl methacrylate) (PDMS‐PTMPM) diblock copolymers . Upon oxidation of the PTMPM moiety to PTMA, the radical polymer‐containing PDMS‐PTMA diblock copolymer was readily obtained.…”
Section: Radical Polymersmentioning
confidence: 99%